Daya Guna Buah Bit (Beta vulgaris L) Sebagai Terapi Antihipertensi - Ghania Uliviana Azizah Alizar (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Hypertension is still a global problem today, this is because hypertension can be the precursor to other non-communicable diseases. The use of medicines derived from plants is an alternative in the way of treating a disease. Apart from being easy to reach, the price is relatively cheaper, the use of ingredients from plants has fewer side effects than modern medicines. One of the uses is the use of beets (Beta vulgaris L.) in lowering blood pressure. Purpose: to find out more about the effects of beets on lowering blood pressure. Method: collecting scientific articles from previous research and conducting literature reviews on these sources. Result: Nitrate and potassium content in beets play a role in the process of regulating the relaxation of vascular smooth muscle and plasma volume in the body. Conclusion: Based on the literature review that has been done, it can be concluded that the nutritional content in beets has factors that can help lower blood pressure.